2020
DOI: 10.3390/ph13070151
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Repeated Administration of Parenteral Ketamine for Depression

Abstract: The objective of this study was to investigate the safety of repeated parenteral ketamine for depression. An electronic survey inquiring about the frequency of adverse events was distributed to providers of parenteral ketamine for depression. In addition, the investigators conducted a search of published studies describing six or more repeated parenteral ketamine treatments administered to individuals for depression, and extracted reported adverse events. The survey was sent to 69 providers, of which 36 respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…To summarize, the advantages of using ketamine or esketamine can be recapitulated as the following: (i) no requirement for daily administration, as the molecules are administered for limited periods, thereby increasing a patient's compliance and reducing the stigma of prolonged and daily intake of medications; (ii) the availability of nasal spray formulations that, in the case of esketamine, provide better handling and fewer safety profile issues and side effects; and (iii) in the case of concomitant medications, the possibility to reduce doses, thereby again improving safety profiles and reducing side effects [11,101].…”
Section: Possible Advantages Of Ketamine and Esketamine Compared With Current Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize, the advantages of using ketamine or esketamine can be recapitulated as the following: (i) no requirement for daily administration, as the molecules are administered for limited periods, thereby increasing a patient's compliance and reducing the stigma of prolonged and daily intake of medications; (ii) the availability of nasal spray formulations that, in the case of esketamine, provide better handling and fewer safety profile issues and side effects; and (iii) in the case of concomitant medications, the possibility to reduce doses, thereby again improving safety profiles and reducing side effects [11,101].…”
Section: Possible Advantages Of Ketamine and Esketamine Compared With Current Treatmentsmentioning
confidence: 99%
“…In addition, increasing evidence now points to its therapeutic efficacy in treatment-resistant depression (TRD), as well as a potential agent for reducing and preventing suicide in depressed patients, as it exerts rapid antidepressant properties as early as several hours after administration. This contrasts with traditional antidepressants (e.g., selective serotonin reuptake inhibitors [SSRIs]), that usually require several weeks for clinical responses [9][10][11][12][13][14][15]. An intranasal formulation of esketamine, currently branded as Spravato ® , was approved by the Food and Drug Administration (FDA) in the United States in March 2019, and by the European Commission in December 2019, for [16,17] the treatment of TRD, defined as the lack of response to two or more adequate trials of antidepressant medications in a current moderate to severe depressive episode [12,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The antidepressant effect of ketamine persists days or weeks beyond treatment, and the assumption may be that the rapid effect will appear, nevertheless, in subsequent ketamine treatment ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] A recently published study also concluded that the incidence of adverse effects was low and ketamine is reasonably safe even in the long-term treatment of patients with depression based on the survey and the published studies. [ 3 ] It is important to note that the survey included specialists of diverse groups and the most common route of administration of ketamine was intravenous in the published reports. [ 3 ] Therefore, I believe that low-dose ketamine infusion is safe if it is used under proper monitoring by trained care providers.…”
mentioning
confidence: 99%
“…[ 3 ] It is important to note that the survey included specialists of diverse groups and the most common route of administration of ketamine was intravenous in the published reports. [ 3 ] Therefore, I believe that low-dose ketamine infusion is safe if it is used under proper monitoring by trained care providers. The addition of a benzodiazepine (preferably midazolam) would negate the unwanted, fortunately, transient psychotomimetic effects of ketamine, while anticholinergics (preferably glycopyrrolate) may be administered if excessive secretions are troublesome according to the patient's hemodynamic parameters.…”
mentioning
confidence: 99%